Proceedings IEEE Thirteenth Annual International Conference on Micro Electro Mechanical Systems (Cat. No.00CH36308)
DOI: 10.1109/memsys.2000.838491
|View full text |Cite
|
Sign up to set email alerts
|

A check-valved silicone diaphragm pump

Abstract: Two generations of check-valved silicone rubber diaphragm pumps are presented. Significant improvements have been made from pump to pump including the design and fabrication of a double-sided check valve, a bossed silicone membrane, and silicone gaskets. Water flow rates of up to 13 ml/min and a maximum back pressure of 5.9 kPa were achieved through pneumatic operation with an external compressed air source. Using a custom designed solenoid actuator, flow rates of up to 4.5 ml/min and a maximum back pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…The magnetically actuated reciprocating micropump has also been studied by Shinozawa et al (1997) and Meng et al (2000).…”
Section: Reciprocating Typementioning
confidence: 99%
“…The magnetically actuated reciprocating micropump has also been studied by Shinozawa et al (1997) and Meng et al (2000).…”
Section: Reciprocating Typementioning
confidence: 99%
“…Micropumps fabricated with MEMS technology have been considered for use in such fuel transport mechanisms [16][17][18][19][20][21][22][23][24][25][26][27]. Liu et al reported polyimide (PI) diaphragm micropumps (15 × 15 mm 2 ) fabricated using MEMS technology [22].…”
Section: Introductionmentioning
confidence: 99%
“…Zengerle [4] attributes that to the possibility of pumping most fluids where there are no special demands on the electrical properties of the fluid or other significant restrictions. They can be actuated by various mechanisms such as piezoelectric [5 -8], electrostatic [9-11], thermopneumatic [12,13], pneumatic [14,15], shape memory alloy [16], bimetallic [17], and electromagnetic actuations [18,19].Membranes (ie, diaphragms), a critical element in micropumps, have linear and nonlinear operating regions. Compared to the flat membranes, bossed and corrugated membranes can increase the net deflection for equivalent loads and extend the linear operating range.…”
mentioning
confidence: 99%